Inflammasome-IL-1β Signaling Mediates Ethanol Inhibition of Hippocampal Neurogenesis - Crews, Fulton (Frontiers in Neuroscience, 2012)
Abstract Regulation of hippocampal neurogenesis is poorly understood, but appears to contribute to mood and cognition. Ethanol and neuroinflammation are known to reduce neurogenesis. We have found that ethanol induces neuroinflammation supporting the hypothesis that ethanol induction of neuroinflammation contributes to ethanol inhibition of neurogenesis. To identify the key proinflammatory molecule that may be responsible for ethanol-impaired neurogenesis we used an ex vivo model of organotypic hippocampal-entorhinal cortex (HEC) brain slice cultures. Here, we demonstrated a key role of proinflammatory cytokine IL-1β signaling in mediating ethanol inhibition of neurogenesis. Ethanol inhibition of neurogenesis was reversed by neutralizing antibody to IL-1β or blockade of the IL-1β receptor with antagonist IL-1RIa. Ethanol-impaired neurogenesis is associated with strong induction of IL-1β and inflammasome proteins NALP1 and NALP3 in both neurons and astrocytes. Blockade of IL-1β synthesis with inflammasome inhibitors Parthenolide and Bay11708 significantly reversed ethanol inhibited neurogenesis. Furthermore, we also found that IL-1β and inflammasome proteins NALP1 and NALP3 are increased in hippocampal neurons and astrocytes in postmortem alcoholic human brain. Together, these novel findings demonstrate that targeting inflammasome-IL-1β signaling can normalize ethanol-impaired hippocampal neurogenesis, which may have therapeutic implications for treatment of cognitive impairment associated with hippocampal dysfunction in alcoholics.